Optimized uptake time of 18F-THK5351 PET/CT in normal Thai brain - Pachara Thonglim; Chanisa Chotipanich; Prathan Buranasiri (My University, 2019)
Abstract This study investigated 18 F-THK5351 positron emission tomography-computed tomography (PET/CT) images to determine the optimized imaging time of radiopharmaceutical PET/CT in normal Thai population. Seventeen volunteers without any neurological or psychiatric illnesses, who showed no abnormalities upon neurological examination and the standardized uptake value ratio, were included. All subjects were diagnosed using 18 F-THK5351 PET/CT and 3.0 Tesla magnetic resonance imaging (MRI). THK5351 PET/CT was operated on the co-registered MRI to draw a region of interest (ROI). A digital imaging and communications in a medical file were converted to a .img file. Next, the image file was rendered from discrete time to continuous time for plotting graphs. The ROI positions and rendered file were then used to plot a graph showing the relationship between the radiopharmaceutical uptake quantity and the interval time to determine the optimized uptake time of THK5351 PET/CT for the brains of normal Thai population, which was consequently 40–60 min.
Keywords: Medical Imaging Techniques and Applications